(untitled) (Andamios, Revista de Investigación Social, 2014)
Is the disagreement between human and divine law, derived from “judgment”, what lends continuity to the ethical-political community over time? Does the collusion between judgment and guilt protect power in its finitude in the territory of practical life? And in this respect, is it in the incessant movement of contradiction that the insuperable paradox that its re-configuration lies in the perversion of the confinement of the community is revealed? Through these questions, this essay seeks to trace the limits of the speculative discourse in Hegel’s Phenomenology of Spirit in order to rethink the contemporary ethicalpolitical community.